Suicidality, ethnicity and immigration in the United States - Borges, Guilherme (2011)
BACKGROUND: Suicide is the eleventh cause of death in the US. This rate varies across ethnic groups. Whether suicide behavior differs by ethnic groups in the US in the same way as observed for suicide death is a matter of current discussion. The goal of this report is to compare the lifetime prevalence of suicide ideation and attempt among four main ethnic groups (Asians, Blacks, Hispanics, and Whites) in the US. METHODS: Suicide ideation and attempts were assessed using the World Mental Health version of the Composite International Diagnostic Interview. Discrete time survival analysis was used to examine risk for life-time suicidality by ethnicity and immigration among 15,180 participants in the Collaborative Psychiatric Epidemiological Surveys, a group of cross-sectional surveys. RESULTS: Suicide ideation was most common among Non-Hispanic Whites (16.10%), least common among Asians (9.02%), and intermediate among Hispanics (11.35%) and Non-Hispanic Blacks (11.82%). Suicide attempts were equally common among Non-Hispanic Whites (4.69%), Hispanics (5.11%) and Non-Hispanic Blacks (4.15%) and slightly less common among Asians (2.55%). These differences in the crude prevalence rates of suicide ideation decreased but persisted after control for psychiatric disorders, but disappeared for suicide attempt. Within ethnic groups, risk for suicidality was low among immigrants prior to migration compared to the US-born, but equalized over time after migration. CONCLUSIONS: Ethnic differences in suicidal behaviors are partly explained by differences in psychiatric disorders and low risk prior to arrival in the US. These differences are likely to decrease as the US-born proportion of Hispanics and Asians increases.